ANALYSIS OF SURVIVAL OF ORTHOPEDIC METHODS FOR RESTORATION OF TOTAL HARD TISSUE DEFECTS OF TEETH IN THE MANUFACTURE OF FIXED DENTAL CONSTRUCTIONS - Yanishen, I.V.; Fedotova, O.L.; Andrienko, K.Yu.; Khlystun, N.L.; Hermanchuk, S.M. (World of Medicine and Biology, 2024)
The restoration of teeth with significant or complete destruction of the crown tooth part is one of the urgent problems of orthopedic dentistry. The aim of the study was to improve the quality of orthopedic treatment for patients with significant or complete destruction of the crown part of the tooth by analyzing the survival rate of stump pin inserts manufactured using an enhanced methodology. Therefore, the conducted research has demonstrated that the application of our enhanced methodology for fabricating stump pin inserts allows preventing root perforations of supporting teeth and reducing the percentage of inadequate marginal adaptation from 22.4 % to 1.2 %. Overall, the number of complications arising during the usage of CSPI has decreased from 25.3 % to 2.8 %, increasing their survival from 52 % to 96 %. Based on the “Decementation” criterion, survival has increased from 77.5 % to 98.5 %, “Secondary caries process” from 78.5 % to 97 %, and “Root fracture or crack” from 96. 5% to 99.5 %.